The Pathways to College - Lisha Agarwal; Giorgio Brunello; Lorenzo Rocco (Institute of Labor Economics (IZA), 2019)
We estimate the effect of the high school curriculum (or track) on the returns to college using data from the Italian PLUS (Participation Labour and Unemployment Survey) survey. We find that college graduates with vocational high school are less likely to be employed than graduates with academic high school. When employed, they earn 7.3 percent less per hour but work 3.8 percent more hours per week. They are less likely to fill high ranked occupations and more likely to find their first job quickly after school completion than other graduates. The wage penalty associated to vocational education in high school is larger for females than for males and for those born in the less economically developed Southern regions.
Keywords: J24; 330; high school curriculum; returns to college; Italy